2013
DOI: 10.1093/jac/dkt261
|View full text |Cite
|
Sign up to set email alerts
|

A new regimen for continuous infusion of vancomycin during continuous renal replacement therapy

Abstract: This new vancomycin regimen allowed the rapid achievement of target drug concentrations in the majority of patients. CRRT intensity had an influence on vancomycin clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 35 publications
1
68
0
2
Order By: Relevance
“…CoI seems to be more successful under these conditions to achieve the PK/PD targets. The weight-based CoI proposed by Beumier et al (52) achieved an AUC/MIC ratio of Ͼ400 in all patients with a MIC of Յ1 mg/liter and for 72% of patients when the MIC was 1.5 mg/liter. In contrast, the largest vancomycin population PK analysis conducted in patients undergoing CRRT and receiving CoI of vancomycin was not able to quantify the effect of CRRT on vancomycin pharmacokinetics (54).…”
Section: Renal Replacement Therapiesmentioning
confidence: 97%
See 1 more Smart Citation
“…CoI seems to be more successful under these conditions to achieve the PK/PD targets. The weight-based CoI proposed by Beumier et al (52) achieved an AUC/MIC ratio of Ͼ400 in all patients with a MIC of Յ1 mg/liter and for 72% of patients when the MIC was 1.5 mg/liter. In contrast, the largest vancomycin population PK analysis conducted in patients undergoing CRRT and receiving CoI of vancomycin was not able to quantify the effect of CRRT on vancomycin pharmacokinetics (54).…”
Section: Renal Replacement Therapiesmentioning
confidence: 97%
“…Different dosages, either for continuous or intermittent vancomycin therapy, have been proposed in recent PK observational studies (51)(52)(53)(54)(55)(56) to understand the best dosages in patients receiving CRRT. CoI seems to be more successful under these conditions to achieve the PK/PD targets.…”
Section: Renal Replacement Therapiesmentioning
confidence: 99%
“…Numerous pharmacokinetic studies of vancomycin in critically ill patients receiving varying types of RRT have been published (Beumier et al, 2013;Chaijamorn et al, 2011;DelDot et al, 2004;Kielstein et al, 2006;Macias et al, 1991;Petejova et al, 2012bPetejova et al, , 2012c. The vancomycin Sc is reported to be between 0.7 and 0.9 during CVVH/ CVVHDF for effluent flow rates between 20 and 50 mL/min (Chaijamorn et al, 2011;DelDot et al, 2004;Petejova et al, 2012b).…”
Section: Glycopeptidesmentioning
confidence: 99%
“…Indeed such dosing has been validated in one study (Beumier et al, 2013), to increase the achievement of the PK/PD target, AUC/MIC ratio ≥400 (Rybak et al, 2009). Therapeutic drug monitoring to guide dosing is essential, as returning native renal function can increase vancomycin clearance in the presence of CRRT (Macias et al, 1991).…”
Section: Glycopeptidesmentioning
confidence: 99%
“…For example, Beumier and colleagues developed a population pharmacokinetics model for vancomycin administered as a continuous infusion in critically ill patients with sepsis and septic shock, and found that inclusion of CRRT intensity as a covariate on CL significantly improved the model [52]. Similarly, a study by Bilgrami and colleagues specifically targeted patients with high-intensity CRRT (>4 l/hour) receiving meropenem and found that total drug CL was higher compared with previous studies with lower intensity CRRT, intensity being the main parameter that accounted for the differences in meropenem CL ( R 2  = 0.89) [15].…”
Section: Main Limitations Of Available Pharmacokinetic Studiesmentioning
confidence: 99%